Development and characterization studies of Eu3+-doped Zn2SiO4 phosphors with waste silicate sources - Sheh Omar, Nur Alia; Yap, Wing Fen; Matori, Khamirul Amin; Abdul Aziz, Sidek; Nadakkavil Alassan, Zarifah; Samsudin, Nur Farhana (Elsevier, 2016)
Structures, morphologies, and properties of europium doped zinc silicate were characterized using X-ray diffractometer, Field emission scanning electron microscope, Fourier transform infrared spectrometer, and UV-vis spectrophotometer. The density of doped zinc silicate shows the trend of increment when the sintering temperature increases. The XRD pattern shows that the material was highly crystalline, having sharp peaks, while the FESEM image reveals the presence of densely packed grains as sintering temperature increased 600 ̊C up to 1000 ̊C. The increase of transmission band intensities at 3443, 1630, 980, 650, 530 cm-1 confirmed the crystallization of Zn2SiO4 crystal in the glass matrix with increasing sintering temperature. Lastly, the increment of energy band gap after sintering temperature at 900 ̊C was related to the stabilization of α-Zn2SiO4 phase in material.